(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2021)
Introduction: Spontaneous intracerebral hemorrhage (ICH) comprises 10-15% of all strokes. Aim: To assess the relationship between the haematoma volume and early surgical outcome of patients with spontaneous primary supratentorial intracerebral hemorrhage by Glasgow Outcome Scale at the 30th post ictus day. Methods: This prospective study was done from April 2014 to March 2016 in Department of Neurosurgery, Combined Military Hospital (CMH), Dhaka. Forty seven cases were selected by set down criteria. Glasgow Coma Scale (GCS) score was recorded on admission, haematoma volume was calculated from the CT scan immediately after admission by Modified Ellipsoid Method and the surgical outcome of ICH patients was determined by Glasgow Outcome Scale (GOS) by face to face interview or by structured interview over phone at their 30th post ictus day. Correlation between the haematoma volume and the surgical outcome of ICH was done by Chi-square test. Again the correlations of three variables (haematoma volume, admission GCS and ICH score) with GOS was compared by Spearman’s correlation coefficient test. Results: Patients with haematoma volume of 30cc or more were found to have worst outcome. Conclusion: Relationship between haematoma volume and surgical outcome was found statistically very significant. Risk stratification of the patients with spontaneous primary supratentorial intracerebral hematomas basing on hematoma volume may be used to improve standardization of treatment protocols and clinical research studies. JAFMC Bangladesh. Vol 15, No 1 (June) 2020: 46-49